2020
DOI: 10.1016/j.bpc.2020.106452
|View full text |Cite
|
Sign up to set email alerts
|

Host-membrane interacting interface of the SARS coronavirus envelope protein: Immense functional potential of C-terminal domain

Abstract: The Envelope (E) protein in SARS Coronavirus (CoV) is a small structural protein, incorporated as part of the envelope. A major fraction of the protein has been known to be associated with the host membranes, particularly organelles related to intracellular trafficking, prompting CoV packaging and propagation. Studies have elucidated the central hydrophobic transmembrane domain of the E protein being responsible for much of the viroporin activity in favor of the virus. However, newer insights into the organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 138 publications
(183 reference statements)
0
42
0
2
Order By: Relevance
“…However, this region corresponds to the transmembrane domain. Interestingly, for the envelope (E) protein in SARS-CoV-1, amyloidogenic sequences at the C-terminus were also previously noted [ 258 ]. The same work discusses the possible role of the amyloidogenic sequence in the performance of protein E of its functions of binding to the host cell membranes and formation of ion channels.…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 94%
“…However, this region corresponds to the transmembrane domain. Interestingly, for the envelope (E) protein in SARS-CoV-1, amyloidogenic sequences at the C-terminus were also previously noted [ 258 ]. The same work discusses the possible role of the amyloidogenic sequence in the performance of protein E of its functions of binding to the host cell membranes and formation of ion channels.…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 94%
“…These changes may occur due to specific inter-molecular interactions of the E-CTD with lipid molecules or salt-bridge interactions, or intra-chain hydrogen bonds [4]. The E-CTD contains the highly conserved cysteine-containing motif CxxC that may allow disulfide isomerization to enhance membrane-directed conformational changes [19].…”
Section: Conformational Properties Of the E-ctd In The Presence Of LImentioning
confidence: 99%
“…In SARS-CoV-2, it has been shown that the envelope protein (E) can promote changes in the properties of lipid membranes of the secretory organelles of the host cells, which help in packaging and releasing the new viral particles [3,4]. E has thus a dual role, since it acts both as a structural protein, being an essential part of the viral capsid, and as a modulator of the cell membrane properties of the host cell during the replication of the virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteome structure of SARS-CoV-2 consists of four structural proteins, two polyproteins and possibly nine accessory proteins [ 4 ]. The four structural proteins are Spike protein (S), Nucleocapsid protein (N), Membrane protein (M) and Envelope protein (E) which majorly responsible for viral assembly to virion structure constructions and maintaining structural integrity [ 5 ]. Interestingly, these protein sequences are highly similar to the sequences of the corresponding protein of SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%